BODIPY Conjugate of Epibrassinolide as a Novel Biologically Active Probe for In Vivo Imaging - Starodubtseva, Anastasiia; Kalachova, Tetiana; Iakovenko, Oksana; Stoudková, Vera; Zhabinskii, Vladimir; Khripach, Vladimir; Ruelland, Eric; Martinec, Jan; Burketová, Lenka; Kravets, Volodymyr (International journal of molecular sciences, 2021)
Brassinosteroids (BRs) are plant hormones of steroid nature, regulating various developmental and adaptive processes. The perception, transport, and signaling of BRs are actively studied nowadays via a wide range of biochemical and genetic tools. However, most of the knowledge about BRs intracellular localization and turnover relies on the visualization of the receptors or cellular compartments using dyes or fluorescent protein fusions. We have previously synthesized a conjugate of epibrassinolide with green fluorescent dye BODIPY (eBL-BODIPY). Here we present a detailed assessment of the compound bioactivity and its suitability as probe for in vivo visualization of BRs. We show that eBL-BODIPY rapidly penetrates epidermal cells of Arabidopsis thaliana roots and after long exposure causes physiological and transcriptomic responses similar to the natural hormone.
Keywords: fluorescenční barviva; signální transdukce; plant bioassay; Fluorescent Dyes; sloučeniny boru; Signal Transduction; regulátory růstu rostlin; Boron Compounds; Plant Roots; live imaging; kořeny rostlin; Steroids, Heterocyclic; brassinosteroids; Brassinosteroids; steroidy heterocyklické; Plant Growth Regulators; fluorescent conjugates; brassinosteroidy; Arabidopsis